Hubungan antara sikap terhadap Fizik dan pencapaian Matematik dengan pencapaian Fizik pelajar tingkatan empat - Rahimah, Nor (2009)
The aim of this research is to identify students attitude towards Physics. This research also investigated the relationship between students attitude toward Physics and their achievement in Physics and students achievement in Mathematics and their achievement in Physics. This research focus on six variable, which is attitude towards Physics, carier in Physics, important of Physics, difficulty of Physics, Physics teacher and Physics equipment. The respondens were 203 form four students in science stream and take Physics subject as electives subject. This research was survey in Sekolah Menengah Kelas Rancangan Khas Daerah kota Bharu, Kelantan. A questionnaire was used to collect the data regarding six aspect (24 items). The item from Prokop, Tuncer and Chuda (2007) was translated and were used to determine the students attitude towards Physics. The collected data were analyzed using the SPSS version 12.0 for windows software. Result showed that male and female students attitude towards their Physics teacher and the important of Physics is high, but male and female students attitude towards difficulty of Physics is low. There was significant difference between students interest towards Physics, student attitudes towards career in Physics, the difficulty of Physics, Physics teacher and Physics equipment. There was no significant difference between students attitude towards the important of Physics and achievement in Physics. There was strong relationship between students interest towards Physics, students attitude towards difficulty of Physics and their achievement in Mathematics with their achievement in Physics. This indicate that the more positives students attitude towards Physics the higher their achievement in Physics. The higher students achievement in Mathematics, the higher their achievement in Physics. Several recommendations were made at the end of the report on ways educators could accommodate the students attitude towards Physics as well as ways to improve students achievement in Physics. The recommendations are, Physics teacher needs to identify their students attitude to motivate their student to practice positive attitudes towards Physics. Physics and Mathematics teacher also needs to take strategies to increase student achievement in Physics and Mathematics.